Resilience in Student Research - Mohamed Razif, Noor Adeebah (Trinity Student Medical Journal, 2022)
Since early 2020, the world witnessed SARS-CoV-2—the COVID-19 virus—taking away the lives of their loved ones and stopping many large in-person gatherings such as going to the cinemas, conferences, and in-person lectures. Research done by students was also one of the activities that was inevitably affected by the pandemic. Many aspiring student researchers faced a halt to their exciting scientific investigations for the remaining academic year and their upcoming summer break unless they were essential or related to COVID-19. Various organised studentships and research programmes had to be cancelled too. This is largely because this research requires physical presence in a laboratory or physical interaction with patients. However, this did not bring student researchers down—their resilience shined through. In the past year, students around the world managed to make the most out of lockdowns and restrictions by carrying out research in the most accessible way they could, as demonstrated by the contents of this 21st volume of the TSMJ.